Pengembangan E-Modul Berbasis Inkuiri Terbimbing Terintegrasi Multirepresentasi dan Virtual Laboratory pada Materi Larutan Elektrolit dan Nonelektrolit untuk Kelas X SMA/MA - Annisatul Aulia; Andromeda Andromeda (Universitas Negeri Padang, 2019)
Electrolyte and non-electrolyte solutions are materials consisting of theory and practicum so that teaching materials are needed that can support the characteristics of this material. The purpose of this study is to produce teaching materials in the form of integrated multi-representation and virtual laboratory based e-modules based on electrolyte and non-electrolyte solution material, and reveal the validity and practicality of the modules produced. This type of research is Research and Development and uses a 4-D model which includes four stages, including the define, design, develop, and disseminate stages (at this stage not done). The validity test was carried out by three chemistry lecturers at FMIPA UNP and two chemistry teachers at SMAN 4 Pariaman using an instrument in the form of a validity questionnaire. Practical tests were carried out by three high school chemistry teachers and 25 students of class X IPA 1 in SMAN 4 Pariaman using an instrument in the form of a practical questionnaire. The average kappa moment (k) the results of the validity and practicality tests by the teacher and students of e-modules are 0.90; 0.98; 0.83 with a very high validity category, the practicality category of teachers is very high, and the practicality category of students is very high. The data shows that integrated guided inquiry-based e-modules are multi-representation and virtual laboratory on electrolyte and non-electrolyte solution material are valid and practical